New insights into the phylogeny and infrageneric taxonomy of Saussurea based on hybrid capture phylogenomics (Hyb-Seq) - Liansheng Xu; Zhuqiu Song; Tian Li; Zichao Jin; Buyun Zhang; Siyi Du; Shuyuan Liao; Xingjie Zhong; Yousheng Chen (Plant Diversity)
Saussurea is one of the largest and most rapidly evolving genera within the Asteraceae, comprising approximately 520 species from the Northern Hemisphere. A comprehensive infrageneric classification, supported by robust phylogenetic trees and corroborated by morphological and other data, has not yet been published. For the first time, we recovered a well-resolved nuclear phylogeny of Saussurea consisting of four main clades, which was also supported by morphological data. Our analyses show that ancient hybridization is the most likely source of deep cytoplasmic-nuclear conflict in Saussurea, and a phylogeny based on nuclear data is more suitable than one based on chloroplast data for exploring the infrageneric classification of Saussurea. Based on the nuclear phylogeny obtained and morphological characters, we proposed a revised infrageneric taxonomy of Saussurea, which includes four subgenera and 13 sections. Specifically, 1) S. sect. Cincta, S. sect. Gymnocline, S. sect. Lagurostemon, and S. sect. Strictae were moved from S. subg. Saussurea to S. subg. Amphilaena, 2) S. sect. Pseudoeriocoryne was moved from S. subg. Eriocoryne to S. subg. Amphilaena, and 3) S. sect. Laguranthera was moved from S. subg. Saussurea to S. subg. Theodorea.